Harry Potter and the sorcerer's stone - Rowling, J.K. (New York : Scholastic Inc, 1998)
Rescued from the outrageous neglect of his aunt and uncle, a young boy with a great destiny proves his worth while attending Hogwarts school of witchcraft and wizardy.
Keywords: Fantasy -- fiction; Witches -- fiction; Wizards -- fiction; Schools -- fiction